Sources of finance for development - Wilfried Guth (Intereconomics, 1979)
The foreign capital requirements of less developed countries (LDCs) are basically the result of their huge volume of investment which far exceeds their actual saving potential. In addition, their capital needs are steadily rising owing to inflation and—not least—to the higher cost of energy. As there is no standard recipe for development finance, the following article gives a survey of the major sources of capital.
Keywords: 330; Financing